Knowledge, Attitude, and Practice Regarding Physical Activity Among Type 2 Diabetic Patients Attending a Tertiary Care Hospital - Aryal, Nirmala; Byahut, Jesika; Thapa, Mamta; Roka, Tara; Pandey, Manju (Medical Journal of Shree Birendra Hospital, 2025)
Introduction: Diabetes Mellitus is one of the top priority non-communicable diseases. Regular physical activity plays a significant role in patients with diabetes in improving blood glucose levels, and insulin sensitivity as well as in the reduction of morbidities and complications related to diabetes mellitus. The objective of the current study was to identify the Knowledge, Attitude, and Practice regarding physical activity among type 2 diabetes mellitus patients. Methods: A descriptive cross-sectional study with a sample size of 206 was adopted. A purposive sampling technique was used to select the sample. A semi-structured questionnaire and the International Physical Activity Questionnaire (IPAQ) were used. Collected data were analyzed using both descriptive and inferential statistics. Results: We found 37.4% of the patients had good knowledge regarding physical activity, 4.9% of patients had good practice of physical activity and only 5.3% had positive attitude towards physical activity. There was a weak negative correlation (r= -0.194) between knowledge and attitude toward physical activity and there was a significant relationship between knowledge and practice at 99% CI (p=0.005). But neither knowledge nor attitude were significantly correlated with practice. We found an association between the sex and employment status of the patients with the level of knowledge regarding physical activity. This study found a statistically significant association between the level of Practice and the employment status of the respondents. Conclusions: Most of the respondents had poor level of knowledge, negative attitude and poor practice regarding physical activities. There was a weak negative correlation between knowledge and attitude toward physical activity and there was a significant relationship between knowledge and practice. But neither knowledge nor attitude were significantly correlated with practice. There was a significant association between both level of knowledge and level of practice with sex and employment status of the respondents.